Pharmacological and toxicological effects of co-exposure of human gingival fibroblasts to silver nanoparticles and sodium fluoride - Inkielewicz-Stepniak I (Dove Medical Press, 2014)
Iwona Inkielewicz-Stepniak,1,* Maria Jose Santos-Martinez,2–4,* Carlos Medina,2,4 Marek W Radomski2,41Department of Medicinal Chemistry, Medical University Gdansk, Debinki, Poland; 2The School of Pharmacy and Pharmaceutical Sciences, Panoz Institute, Trinity College Dublin, Dublin, Ireland; 3School of Medicine, Trinity College Dublin, Dublin, Ireland; 4Trinity Biomedical Sciences Institute, Trinity College, Dublin, Ireland*These authors contributed equally to this workBackground: Silver nanoparticles (AgNPs) and fluoride (F) are pharmacological agents widely used in oral medicine and dental practice due to their anti-microbial/anti-cavity properties. However, risks associated with the co-exposure of local cells and tissues to these xenobiotics are not clear. Therefore, we have evaluated the effects of AgNPs and F co-exposure on human gingival fibroblast cells.Methods: Human gingival fibroblast cells (CRL-2014) were exposed to AgNPs and/or F at different concentrations for up to 24 hours. Cellular uptake of AgNPs was examined by transmission electron microscopy. Downstream inflammatory effects and oxidative stress were measured by real-time quantitative polymerase chain reaction (PCR) and reactive oxygen species (ROS) generation. Cytotoxicity and apoptosis were measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and real-time quantitative PCR and flow cytometry, respectively. Finally, the involvement of mitogen-activated protein kinases (MAPK) was studied using Western blot.Results: We found that AgNPs penetrated the cell membrane and localized inside the mitochondria. Co-incubation experiments resulted in increased oxidative stress, inflammation, and apoptosis. In addition, we found that co-exposure to both xenobiotics phosphorylated MAPK, particularly p42/44 MAPK.Conclusion: A combined exposure of human fibroblasts to AgNPs and F results in increased cellular damage. Further studies are needed in order to evaluate pharmacological and potentially toxicological effects of AgNPs and F on oral health.Keywords: nanoparticles, oxidative stress, apoptosis, inflammation, mitogen-activated protein kinases, matrix, metalloproteinases